Merger Speculation in Financial Media: The Valuation of Investigative Reporting. Issue 3 (3rd July 2018) - Yost-Bremm, Christopher; Huang, Emily
ABSTRACT: The authors study abnormal returns and volume in the days surrounding takeover speculation by financial media. Significantly positive price and volume responses 2 days after publication are observed. While most of this effect dissipates shortly thereafter, some excess returns remain impounded into the stock price. A study of the ex post takeover probabilities suggests that a positive response is justified, as takeover probabilities for such firms subsequently increase. This evidence is consistent with the idea that financial media speculation can facilitate the release of useful private information to shareholders. However, significantly positive excess returns and volume in the few days before publication also suggests that certain shareholders may benefit disproportionately.